Influence of Clinician-Related Factors on Adherence to the American Heart Association Guidelines for Acute Coronary Syndrome among Clinicians at Kenya Ports Authority Clinics in Mombasa, Kenya - Mailu, Mary; Shariff, Nilufa; Mbugua, Ruth (Journal of Health, Medicine and Nursing, 2024)
Purpose: The aim of the study was to assess influence of clinician-related factors on adherence to the American heart association guidelines for acute coronary syndrome among clinicians at Kenya Ports Authority clinics in Mombasa, Kenya. Methodology: A descriptive cross-sectional study involving quantitative methods of data collection was adopted. An interviewer administered questionnaire was used for data collection. The study was carried out in Kenya Ports Authority clinics in Mombasa, Kenya. The target population was 106 clinicians attending to patients who present with Acute Coronary Syndrome at the KPA clinics in Mombasa. A census method was used to determine the study participants. The sample size was made up of a hundred and six participants. The clinicians who consented to participate in the study were included while those who were on sick off, leave or who recently joined the clinic were excluded. Pretesting of the study tool was done at the Kenya Pipeline Clinic Mombasa. Data analysis was done using Statistical Package for Social Sciences version 25 and presented via tables. Findings: The study results showed that at 95% level of confidence (Ï-value = 0.05%), there was a significant association between gender (á¾³=0.025), work experience (á¾³=0.016), job cadre (á¾³=0.014) and training received (á¾³=0.022) on adherence to the American Heart Association Guidelines for Acute Coronary Syndrome among clinicians at Kenya Ports Authority clinics in Mombasa, Kenya. The association was insignificant between age (á¾³=0.178), education level (á¾³=0.439) and specialization (á¾³=0.489) on adherence to the AHA guidelines. Unique Contribution to Theory, Practice and Policy: The study recommends that the KPA management should increase the medical budget to ensure availability of adequate resources for ACS patient management. These resources include adequate staffing, medication, equipment, and staff training costs. The clinic management should ensure that medications such as aspirin, morphine and nitroglycerine are readily available and accessible at patients care points. The KPA clinic management to formulate a simple algorithm that outlines the steps to be taken when managing ACS patients. The study recommends that the clinics should assess their equipment reqularly for maintenance controls to ensure efficiency. The study further recommends random assessments and post care audits to assess the adherence to ACS guidelines among clinicians. Training associated with adherence to the AHA guidelines and as such, KPA should continue offering training and education on the latest AHA guidelines for ACS to ensure updated guidelines for practice.